The power of open-book management : releasing the true potential of people's minds, hearts, and hands - Schuster, John P.; Carpenter, Jill (New York : John Wiley, 1996)
Business
Keywords: Open-book management; Organizational effectiveness; Organizational learning; Management-Employee participation; Incentives in industry; Business education; Planning